2018
DOI: 10.1136/bcr-2018-227862
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic adenocarcinoma of mandible: in search of the primary

Abstract: We present here a case of a 64-year-old female patient who reported with a complaint of pain in the chin region of 3-month duration. The radiographs revealed an irregular radiolucent lesion in the anterior part of the mandible. An incisional biopsy was carried out and the microscopy showed features of adenocarcinoma. Suspecting a metastatic lesion, the patient was then sent for whole body examination which showed a mass in the lungs. A whole body scan also showed metastasis to other organs such as kidney, gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…19,27 Metastatic lesions can be found anywhere in the oral cavity, yet 90% of them have an intraosseous localization, while soft tissue localizations are rare. 28 Labrador et al in a more recent review estimate that osseous invasion corresponded to 65%-75% of the cases, while soft tissue invasion corresponded to 25%-35%. It is quite impossible to determine whether these are primarily soft tissue or bone tissue lesions because it is often a combination of soft and bone tissue involvement.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…19,27 Metastatic lesions can be found anywhere in the oral cavity, yet 90% of them have an intraosseous localization, while soft tissue localizations are rare. 28 Labrador et al in a more recent review estimate that osseous invasion corresponded to 65%-75% of the cases, while soft tissue invasion corresponded to 25%-35%. It is quite impossible to determine whether these are primarily soft tissue or bone tissue lesions because it is often a combination of soft and bone tissue involvement.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, Kanth et al suggested that the main mechanism of hematogenous metastasis to the oral cavity involves Batson's venous plexus, the valveless prevertebral venous network that permits the retrograde path of tumour cells from the lungs to the face 19,27 . Metastatic lesions can be found anywhere in the oral cavity, yet 90% of them have an intraosseous localization, while soft tissue localizations are rare 28 . Labrador et al in a more recent review estimate that osseous invasion corresponded to 65%–75% of the cases, while soft tissue invasion corresponded to 25%–35%.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cavity metastasis typically has a poor prognosis, with most patients dying within one year of diagnosis (35)(36)(37)(38)(39)(40)(41)(42)(43). The prognosis depends on the treatment of the oral cavity lesion, as well as adequate control of the primary tumor and metastasis (advanced disease) (35)(36)(37)(38)(39)(40)(41)(42)(43)52).…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent literature review primarily focused on studies published in English, although those published in other languages were also evaluated for relevance and new information. No restrictions regarding the publication date were applied, with the earliest study being published in 1961, and the findings of the literature search were summarized in Table II (35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Literature Search Strategy Multiple Databases Includingmentioning
confidence: 99%
“…4 Metastatic lesions can be found anywhere in the oral cavity, yet 90% are intraosseous and within the mandible and soft tissue localizations are rare. 5 Metastatic foci in the jaw bones are mainly situated in the red marrow, where there is hematopoietically active bone marrow. 6 The ascending ramus and angle of the posterior mandible as well as focal osteoporotic bone marrow defects are the most hematopoietically active sites that attract tumor cells, thus accounting for their higher tendency to seed within these sites.…”
Section: Discussionmentioning
confidence: 99%